Blunt carotid injury from a penetrating stick: an unexpected injury. (22nd July 2010) - Wijeyaratne, S M; Weerasinghe, C; Cassim, M R N
Abstract : Unattended blunt carotid injury (BCI) has stroke high risk of stroke and screening based on injury probability is recommended. Penetrating forces are not considered high risk and concomitant BCI would go unattended. The authors report a case of a 48-year-old man who fell out of a tree on to an upright stick that penetrated his lateral neck. He presented with impalement, which was removed after surgically laying open the entire wound. The carotid sheath had been breached and the internal jugular vein was bleeding. The adjacent common carotid artery was intact and pulsating with no external evidence of injury. However, injury proximity led to vascular imaging that demonstrated intimal disruption without thrombus or stenosis. Although he remained asymptomatic on heparin, the injury progressed to cause significant lumen stenosis. Endovascular stenting re-established the vessel lumen and he remains well on aspirin 9 months later. Awareness that penetrating neck trauma may cause BCIs is important.